The Republican party in the age of Roosevelt : sources of anti-government conservatism in the United States - Rosen, Elliot A., 1928- (UPCC book collections on Project MUSE., 2014)
Elliot Rosen's Hoover, Roosevelt, and the Brains Trust focused on the transition from the Hoover administration to that of Roosevelt and the formulation of the early New Deal program. Roosevelt, the Great Depression, and the Economics of Recovery emphasized long-term and structural recovery programs as well as the 1937-38 recession. Rosen’s final book in the trilogy, The Republican Party in the Age of Roosevelt, situates distrust of the federal government and the consequent transformation of the party. Domestic and foreign policies introduced by the Roosevelt administration created division between the parties. The Hoover doctrine, which sought to restrict the reach of independent agencies at the federal level in order to restore business confidence and investment, intended to reverse the New Deal and to curb the growth of federal functions.